Rediscovering digitules in Aphidomorpha and the question of homology among Sternorrhyncha (Insecta, Hemiptera) - Metz, Mark A. (Zookeys, 2017)
Abstract. We explore and expand on the morphological term digitule. The term was originally proposed for toe-like setae on a species of Phylloxera Boyer de Fonscolombe, 1834 (Hemiptera, Sternorrhyncha, Aphidomorpha) by Henry Shimer, an American naturalist. While it is standard terminology in scale systematics (Hemiptera, Sternorrhyncha, Coccidomorpha), the term digitule was ignored by aphid specialists despite being the original taxon for which the term was described. Similar setae occur on many arthropod groups, so the homology is poorly understood even within any superfamily of Hemiptera. We provide the etymology of the term, a proposed explanation for why it was used among scale taxonomists and not aphid taxonomists, and discuss briefly options to progress beyond the confusion between terminology for morphology and homology in Sternorrhyncha.